APLIKASI SISTEM INFORMASI GEOGRAFI (SIG) DAN METODE GEOLISTRIK DALAM PEMBUATAN PETA RAWAN LONGSOR DI KECAMATAN ALLA KABUPATEN ENREKANG - Irmayanti Irmayanti; Muh Said L; Ayusari Wahyuni (Universitas Islam Negeri Alauddin Makassar, 2020)
This research was conducted Alla district, Enrekang regency. This study aims to isolate or zoning areas prone to landslides using GIS software and identify the causes of landsileds using the wenner-schlumberger configuration geoelectric method in Alla District, Enrekang Regency. Data processing method used is res2dinv software for geoelectric data and arcgis software for mapping and required parameters such as rainfall, slope, geomorphology, soil type and geology. Based on the results obtained by using GIS application by overlapping land type map, geology, slope slope, geomorphology and rainfall, then obtained landslide inecology rate in the research area namely for low inecology rate with an area of 12% spread percentage, for moderate inewanity rate with an area of 57% dispersal percentage and for high inwant rate with an area of 30% spread percentage. Results obtained using geoelectric methods found the discovery of a potential landslide slip field. This guessing is due to the three layers in the research area there is a slip field with a resistivity value of 29.7 Ωm – 37.9 Ωm. The data of the research results using GIS application is reinforced by the data of previous research by using geoelectric methods in Pana village of Alla District Enrekang Regency Keywords: SIG, Landslide, Geoelectric, Software Arcgis.